Ferumoxytol-Enhanced Cardiac Magnetic Resonance Angiography and 4D Flow: Safety and Utility in Pediatric and Adult Congenital Heart Disease - Pierangelo Renella; Jennifer Li; Ashley E. Prosper; J. Paul Finn; Kim-Lien Nguyen (MDPI AG, 2022)
Cardiac magnetic resonance imaging and angiography have a crucial role in the diagnostic evaluation and follow up of pediatric and adult patients with congenital heart disease. Although much of the information required of advanced imaging studies can be provided by standard gadolinium-enhanced magnetic resonance imaging, the limitations of precise bolus timing, long scan duration, complex imaging protocols, and the need to image small structures limit more widespread use of this modality. Recent experience with off-label diagnostic use of ferumoxytol has helped to mitigate some of these barriers. Approved by the U.S. FDA for intravenous treatment of anemia, ferumoxytol is an ultrasmall superparamagnetic iron oxide nanoparticle that has a long blood pool residence time and high relaxivity. Once metabolized by macrophages, the iron core is incorporated into the reticuloendothelial system. In this work, we aim to summarize the evolution of ferumoxytol-enhanced cardiovascular magnetic resonance imaging and angiography and highlight its many applications for congenital heart disease.